RECREATION AND REHABILITATION CLUSTERS IN UKRAINE: BALANCED SPATIAL ORGANIZATION - Bieloborodova, M. V.; Bezuhla, L. S.; Hladoshchuk, O. G. (Rehabilitation and Recreation, 2024)
The purpose of the study is to substantiate a methodical approach to the clustering of health and rehabilitation tourism in Ukraine based on spatial modeling of the regional resource and material base. Research material: statistical data on the resource and material base of medical and health tourism; cartographic visualization of profile clusters, taking into account the possibilities of tourism revitalization. Methods: abstract-logical and systematic approach, method of structural and logical generalization, method of statistical grouping, graphic method. Results: on the basis of statistical analysis, it is proposed to divide the regions of Ukraine into the following groups: the first – Seaside region (23,2% of the area of Ukraine), specialization – family and children's recreational and health tourism; the second – the Volyn and Carpathian region (13,7%), specializing in sanatorium-resort and rehabilitation with an emphasis on inbound tourism; the third – the Capital and Dnipro-Slobozhansky region (20,4%), specializing in the organization of medical tourism; the fourth – region without a pronounced potential for health and rehabilitation tourism (26,1%); the fifth – region with significant, but insufficiently realized potential in the rehabilitation, medical and health sector (12,3%). The Autonomous Republic of Crimea (4.3% of the area of Ukraine) is separately highlighted as the sixth region, which will require a specific strategy of reintegration into the spatial system of organizing the recreation and rehabilitation economy of post-war Ukraine. Conclusions: to improve the management of rehabilitation, medical, and health tourism, a clustering tool is proposed, taking into account the possibilities of tourism revitalization of the relevant objects. The regions of Ukraine are divided into six groups according to the level of development of the resource and material base, each of which has a clear specialization and target group of tourists, as well as the direction of strategic development. The proposed clustering methodology makes it possible to more efficiently distribute resources between regions, focusing on their unique capabilities while concentrating efforts on the development of those areas where a certain region has the greatest potential. Clustering also allows better integration of tourism and medical infrastructure, increasing service provision and availability for socially vulnerable population groups.